FIREPLACE AS A HISTORICAL INDICATOR OF CLIMATE CHANGE: THE DEVELOPMENT OF HEATING TECHNOLOGIES IN LATE MEDIEVAL AND EARLY MODERN EUROPE - BATENKO, Taras (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
This article examines the historical development of heating technologies in the context of climate changes in Late Medieval and Early Modern Europe. The study of fireplaces, blast furnaces, and cast-iron plates, which served as primitive radiators, traces how societies adapted to the climatic challenges of the Little Ice Age. Prolonged deviations in average temperatures during this period triggered changes in heating methods, including the modernization of wall fireplaces, the introduction of hydraulic hammers, and the advancement of blast furnaces powered by hydraulic energy. These innovations enabled Europeans to produce cast-iron fireplace and stove plates for supplementary heating. Special attention is given to early types of fireplaces, whose designs evolved from open hearths located at the center of rooms to corner and wall fireplaces typical of medieval castles. The emergence of fireplaces placed against a house's central supporting wall, equipped with chimneys and hoods, marked a significant scientific and technical breakthrough in medieval Europe. These fireplaces could be constructed on multiple levels within castles and abbeys, showcasing the engineering innovations of the era. The research is based on historical accounts, archaeological evidence, and textual sources, including works by French historians. Archival documents from the 15th–16th centuries describe the development of heating technologies, including the reconstruction and repair of fireplaces in castles and abbeys. The article emphasizes the use of «proxy» data for reconstructing climate changes and their impact on socio-economic development. The analysis of material culture, particularly fireplaces and stoves, offers new perspectives for studying climatic trends and their implications for daily life, technology, and architecture of the period.